2022
DOI: 10.4315/jfp-21-444
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Antimicrobial Resistance of Vibrio parahaemolyticus in Retail Seafood in Hanoi, Vietnam

Abstract: Vibrio parahaemolyticus is a major cause of foodborne diseases and a significant threat to human health worldwide. Most of the infections caused by V. parahaemolyticus are usually associated with the consumption of raw or undercooked seafood. This study was conducted to determine the prevalence, quantitative load, and antimicrobial resistance of V. parahaemolyticus in retail seafood in Hanoi, Vietnam. A total of 120 seafood samples consisting of marine fish (n = 30), oysters (n = 30), shrimp (n = 30), and squi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Our study demonstrated a high prevalence of AMR phenotypes among the 36 V. parahaemolyticus isolates for ampicillin (83%, 30/36) and colistin (100%, 36/36), which was in consistent with the frequent outbreaks of ampicillin- and colistin-resistant V. parahaemolyticus isolates reported in the past 5 years ( Lopatek, Wieczorek & Osek, 2018 ; Dahanayake et al, 2020 ; Mok et al, 2021 ; Nishino et al, 2021 ; Vu et al, 2022 ). The blaCARB gene was present in all 36 V. parahaemolyticus isolates, confirming ampicillin-resistant phenotypes and susceptible phenotypes to amoxicillin/clavulanic acid, ampicillin/sulbactam, and piperacillin/tazobactam.…”
Section: Discussionsupporting
confidence: 88%
“…Our study demonstrated a high prevalence of AMR phenotypes among the 36 V. parahaemolyticus isolates for ampicillin (83%, 30/36) and colistin (100%, 36/36), which was in consistent with the frequent outbreaks of ampicillin- and colistin-resistant V. parahaemolyticus isolates reported in the past 5 years ( Lopatek, Wieczorek & Osek, 2018 ; Dahanayake et al, 2020 ; Mok et al, 2021 ; Nishino et al, 2021 ; Vu et al, 2022 ). The blaCARB gene was present in all 36 V. parahaemolyticus isolates, confirming ampicillin-resistant phenotypes and susceptible phenotypes to amoxicillin/clavulanic acid, ampicillin/sulbactam, and piperacillin/tazobactam.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, significant levels of antibiotic residues, including ampicillin, erythromycin, and tetracycline, have been detected in aquaculture water in Vietnam, which may contribute to the increasing resistance rates to these antimicrobials [ 37 ]. Conversely, other studies have shown that ampicillin, tetracycline, and erythromycin were effective against V. parahaemolyticus strains, with over 90% of isolates being inhibited [ 10 , 38 – 40 ]. The variability in resistance of Vibrio to antibiotics may be attributed to geographical differences or variations in testing methodologies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some V. parahaemolyticus strains are harmful to humans; they were responsible for 25% of seafood-borne diseases in the Can Tho and Tra Vinh provinces in the Mekong Delta in 2015 and 2016 (T. Tran et al, 2018). In a recent study (Vu et al, 2022), V. parahaemolyticus was isolated most frequently from shrimp samples (86.67%), and most of the isolates (85.71%) were resistant to at least one antibiotic tested. The greatest resistance rate was found for ampicillin (81.43%), followed by cefotaxime (11.43%), ceftazidime (11.43%), trimethoprim-sulfamethoxazole (8.57%), and tetracycline (2.86%).…”
Section: Introductionmentioning
confidence: 99%